Interaktiv studentguide : Utveckling av koncept för interaktivt lärande - Karlsson, Douglas (2015)
This report details the development process of an interactive student-guide to be used by students at Luleå University of Technology, developed as a project in Industrial Design Engineering (D7014A). The intention was for the student-guide to motivate, engage and aid students with their learning, which in turn would support their dedication and effort towards becoming independent agents. By applying the ideal that is promoted in Industrial Design Engineering – to put human needs in focus – the aim was for the student-guide to truly be designed according to students’ needs.The methods used during the development process were chosen in order to identify these needs; interviews, focus groups, and discussions were all used for their ability to generate qualitative data. Similarly, the creative methods used were brainwriting and sketching; methods that are easy to get into, but still allow a large amount of freedom. The project as a whole followed an iterative Stage-Gate process, with a focus group discussion at the first, second and third stage. These provided feedback for the current state of the student-guide, and how it should move forward.The final design consisted of an app for smartphones and tablets, with a variety of functions that aimed to streamline the studying experience for students. The main purpose of the app was to gather and summarize important information in one convenient location, as well as to provide an effective way for students to interact with each other. Whether the student-guide would actually create any significant change or not is difficult to say at this point, before it has been tested in practice. However, it was developed based on students’ needs defined through participants of several focus groups, and as such it can probably be relatively safe to say that it would assist at least some students. In order to make the student-guide as appealing as possible to more students however, further work may benefit from re-evaluating the final concept of the student-guide. This should be done ...